A critical discourse analysis of the representation of Ukrainian refugees across the British mainstream news media - Imam Munandar; Saiful Akmal (Universitas Syiah Kuala, 2023)
This research investigates the dominant rhetorical/ discursive strategies in the British mainstream news media regarding their reports on Ukrainian refugees in the United Kingdom (UK). While news media have negatively constructed the non-European refugees, as previous studies have revealed, this research is unique because it specifically focuses on European refugees as its research sample. The ultimate objective was to demonstrate how the news media in the UK portrayed the incoming Ukrainian refugees on British soil. The data were 40 Ukrainian-refugee-related news reports published in four mainstream news media in the UK from March until July 2022. The data was then analysed by using Wodak's Discourse-Historical Approach (DHA), consisting of six analytical categories: Referential, Predication, Argumentation (Topoi), Perspectivisation, Mitigation, and Intensification (Reisigl Wodak, 2008). The research found that regardless of their ideologies, all four news media consistently employed the discursive strategies of humanization and individualization and pervasively established a positive argumentative strategy on Ukrainian refugees. These dominant strategies depict a positive representation of Ukrainian refugees. Moreover, despite the overall negative picture of third-world refugees in British news media, the finding of this research is distinctive from the previous ones, showing that the British news media actively constructed the Ukrainian refugees positively and sympathetically. It is argued that the news media's ideological stance of Eurocentrism and biased racial values played a decisive role in framing the pictures of European/Ukrainian and non-European refugees in their reports.